Does resident involvement in thyroid surgery lead to increased postoperative complications?. (18th October 2016) - Kshirsagar, Rijul S.; Chandy, Zachariah; Mahboubi, Hossein; Verma, Sunil P.
Abstract : Objectives/Hypothesis: To evaluate the impact of resident involvement during thyroid surgery on 30‐day postoperative complications. Study Design: Retrospective cohort study. Methods: All patients who underwent thyroid surgery in 2011 were identified from the American College of Surgeons National Surgical Quality Improvement Program database. Patient demographics, perioperative details, resident involvement in surgery, and 30‐day postoperative complications were extracted. Propensity score analysis was used to match resident and nonresident cases. Univariate and multivariate analysis were performed to determine the relationship between resident involvement in thyroid surgery and postoperative outcomes. Results: One thousand seven hundred forty‐seven patients with and 1, 747 patients without resident involvement were case‐matched for patient demographics, perioperative variables, and surgical case type. There was no significant difference ( P = .19) in 30‐day postoperative complication rates of surgeries with and without resident involvement, which were 1.4% and 2%, respectively. Operative time was longer in surgeries with residents than those without residents (119 ± 67 minutes vs. 102 ± 55 minutes, P < .001). Cases with resident involvement had an unplanned reoperation rate of 0.9%, which was significantly lower than the 2.3% rate of surgeries without residents ( P = .001). Multivariate analysis revealed no significant association between resident involvement and overall complications (odds ratio = 0.70; P = .18). Conclusions: Resident participation in thyroid surgery was not associated with an increased 30‐day postoperative complication rate. These findings demonstrate that patient safety is not adversely affected by resident participation in thyroid surgery. Level of Evidence: 2C Laryngoscope, 127:1242–1246, 2017